The influence of family environment on learning outcomes of grade 5 Students at SDN 002 Tana Tidung - Suhartini Suhartini; Yusuf Hanafi; Sri Rahayuningsih (Journal of Research in Instructional, 2026)
This study aims to determine the influence of the family environment on the learning outcomes of fifth-grade students at SDN 002 Tana Tidung. The family environment plays a crucial role in students' academic development, both in terms of learning motivation, parental involvement, and the family's socio-economic conditions. This study used a qualitative approach with a case study method. Data were collected through semi-structured interviews, participant observation, and documentation studies, involving students, parents, and teachers at SDN 002 Tana Tidung. The results showed that parental attention, communication patterns between parents and children, and support for learning facilities at home played a substantial and observable role in shaping student motivation and learning outcomes. Students from families with democratic parenting styles and open communication tended to have higher motivation and better academic achievement. In addition, families with adequate economic conditions could provide facilities that support the learning process at home, which also improved learning outcomes. This study recommends that schools be more active in exploring the role of families in supporting student learning processes and encouraging parents to be more involved in their children's education. By strengthening collaboration between schools and families, it is hoped that optimal learning outcomes can be achieved for students.